Business education and creation of awareness for disaster risk management in Chile (2016)
This paper discusses the apparent disconnection between disaster risk management research and the lack of tools for business continuity after disastrous events in Chile. As disasters are a common occurrence in business development, local firms are becoming aware of the need for having tools for preparedness and mitigation of negative effects of disasters. Nevertheless, in Chile, this private awareness seems to be part of the business aptitude of large-sized firms rather SMEs. Some of the arguments presented here illustrate this gap between local firms and their need to integrate business continuity management into their business operations and their decision making to cope with disaster risks. In this vein, this document argues the need for innovative academic offerings in Chile and presents a proposal to advance in linking disaster risk management and business education at the University of Chile. This program is developed in the medium-term for each of its components, starting with undergraduate students and achieving major actions with public and private stakeholders in a progressive ladder of initiatives